Development and Validation of Stability Stability-indicating HPLC Method for Related Substances Analysis of Fluorometholone in an Ophthalmic Solution - Sener, Cigdem; Ergen, Harun; Guleli, Muge; Caliskan, Cem (Archives of Case Reports, 2025)
Anti-inflammatory ophthalmic solutions containing fluorometholone (FLM) combinations are commonly used, and very few stability-indicating liquid chromatographic methodshave been reported for their related substances. In this study, a simple HPLC method was developed and validated for the determination of fluorometholone impurities in an ophthalmic solution containing FLM and tetrahydrozoline hydrochloride. All impurities were separated by using gradient elution at a flow rate of 1.5 ml/min using a µBondapak C18 250 mm × 4.6 mm, 5 µm (or equivalent) column kept at 40 °C with 20 µl injection volumes. The wavelength was 240 nm. This method validation included specificity, linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy, precision, and robustness. The stability-indicating capability of this method was evaluated by performing forced degradation stress studies.